Subluminal and superluminal light pulse propagation under external magnetic field in a vee-type three-level atomic medium - Thanh, Thai Doan; Anh, Nguyen Tuan; Hien, Nguyen Thi Thu; Dong, Hoang Minh; Hao, Nguyen Xuan; Khoa, Dinh Xuan; Bang, Nguyen Huy (Photonics Letters of Poland, 2021)
In this work, we investigate subluminal and superluminal light propagation in a vee-type three-level atomic medium under an external magnetic field. The dispersion and absorption behaviors are studied for the cases of absence and presence of a magnetic field. It is found that under an electromagnetically induced transparency condition, the light pulse can be switched between subluminal and superluminal propagation by ON-OFF switching of the magnetic field. Finally, the transient response of the medium is discussed, which shows that the considered scheme has potential applications in magneto-optic switching devices. Full Text: PDF References Boller K J, Imamoglu A, Harris S E, "Observation of electromagnetically induced transparency", Phys. Rev. Lett. 66 (1991) 2593. CrossRef Fleischhauer M, Imamoglu A, Marangos J P, "Electromagnetically induced transparency: Optics in coherent media", Rev. Mod. Phys. 77 (2005) 633. CrossRef L.V. Hau, S. E. Harris, Z. Dutton, C.H. Bejroozi, "Light speed reduction to 17 metres per second in an ultracold atomic gas", Nature, 397 (1999) 594. CrossRef Z. Dutton, N.G.C. Slowe, L.V. Hau, "The art of taming light: ultra-slow and stopped light", Europhysics News, 35 (2004) 33. CrossRef V. Bharti, V. Natarajan, "Sub- and super-luminal light propagation using a Rydberg state", Opt. Commun. 392 (2017) 180-184. CrossRef Khoa D X, Doai L V, Son D H and Bang N H, "Enhancement of self-Kerr nonlinearity via electromagnetically induced transparency in a five-level cascade system: an analytical approach", J. Opt. Soc. Am. B. 31 (2014) 1330. CrossRef Hamedi H R, Gharamaleki A H, and Sahrai M, "Colossal Kerr nonlinearity based on electromagnetically induced transparency in a five-level double-ladder atomic system", Appl. Opt 22 (2016) 5892. CrossRef A. Fountoulakis, A.F. Terzis, E. Paspalakis, "All-optical modulation based on electromagnetically induced transparency", Phys. Lett. A 374, (2010) 3354. CrossRef Khoa D X, Doai L V, Mai Anh L. N, Trung L. C, Thuan P. V, Dung N. T, and Bang N. H, J. "Optical bistability in a five-level cascade EIT medium: an analytical approach", Opt. Soc. Am. B, 33 (2016) 735. CrossRef Hoang Minh Dong, and Nguyen Huy Bang, "Controllable optical switching in a closed-loop three-level lambda system", Phy. Scr. 94, (2019) 115510. CrossRef Dong H M, Doai L V, Sau V N, Khoa D X and Bang N H, "Propagation of a laser pulse in a three-level cascade atomic medium under conditions of electromagnetically induced transparency", Photonics Letter of Poland, 3 (2016) 73. CrossRef Khoa D X, Dong H M, Doai L V and Bang N H, "Propagation of laser pulse in a three-level cascade inhomogeneously broadened medium under electromagnetically induced transparency conditions", Optik 131 (2017) 497. CrossRef H. M. Dong, L.V. Doai, and N.H. Bang, "Pulse propagation in an atomic medium under spontaneously generated coherence, incoherent pumping, and relative laser phase", Opt. Commun. 426 (2018) 553-557. CrossRef Jiahua Li, Rong Yu, Liugang Si, and Xiaoxue Yang, "Propagation of twin light pulses under magneto-optical switching operations in a four-level inverted-Y atomic medium", J. Phys. B: At. Mol. Opt. Phys. 43 (2010) 065502. CrossRef S. H. Asadpour, H. R. Soleimani, "Polarization dependence of optical bistability in the presence of external magnetic field", Opt. Commun 310 (2014) 120-124. CrossRef H.M. Dong, L.T.Y. Nga, and N.H. Bang, "Optical switching and bistability in a degenerated two-level atomic medium under an external magnetic field", App. Opt. 58, (2019) 4192. CrossRef H. M. Dong, L. T. Y. Nga, D. X. Khoa, N. H. Bang, "Controllable ultraslow optical solitons in a degenerated two-level atomic medium under EIT assisted by a magnetic field", Sci. Rep. 10 (2020) 15298. CrossRef Daniel A. Steck, "Rubidium 87D Line Data," http://steck.us/alkalidata. CrossRef